Judicial Accounting and its impact on the outcome of the activity of the Iraqi General Insurance Company: applied research (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to shed light on the importance of forensic accounting and its impact on the outcome of the activity of the Iraqi general insurance company by winning the lawsuits filed against the company because the forensic accountant (the judicial expert) possesses the ability to interpret and analyze the data. The research community represents the insurance companies in Iraq. Iraqi insurance, and the researchers adopted the descriptive approach in covering the theoretical aspect and the deductive approach in covering the practical side, depending on the financial statements of the Iraqi insurance company for the years of research.One of the most important conclusions reached by the researchers was that forensic accounting has an impact on the outcome of the insurance company's activity through winning the lawsuit an not paying compensation or reducing it